2004
DOI: 10.2746/0425164044877198
|View full text |Cite
|
Sign up to set email alerts
|

Epidermal cell proliferation in the equine hoof wall

Abstract: Summary Reasons for performing study: Current theories explaining how the hoof wall ‘grows’ and moves past the stationary distal phalanx are speculative and based on incomplete evidence. Movement in the lamellar region could occur by cell proliferation or an enzyme‐based remodelling process. Since laminitis pathogenesis appears to involve increased transcription and activation of enzymes normally involved in tissue remodelling, it is important to know precisely which process dominates the lamellar region of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
33
2

Year Published

2005
2005
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(37 citation statements)
references
References 16 publications
2
33
2
Order By: Relevance
“…The observations of Daradka and Pollitt [6], who stated that the terminal part of the digital artery enters the solar canal of the distal phalanx via the paired sole foramina and unites with the artery of the opposite side to form the terminal arch deep within the bone, could not be supported by our findings, which showed that there was turning angle instead of terminal arch in yak hoof. Our findings resemble that in cattle [27].…”
Section: Discussioncontrasting
confidence: 97%
See 1 more Smart Citation
“…The observations of Daradka and Pollitt [6], who stated that the terminal part of the digital artery enters the solar canal of the distal phalanx via the paired sole foramina and unites with the artery of the opposite side to form the terminal arch deep within the bone, could not be supported by our findings, which showed that there was turning angle instead of terminal arch in yak hoof. Our findings resemble that in cattle [27].…”
Section: Discussioncontrasting
confidence: 97%
“…The hooves in equine have been frequently mentioned [6,10,13,[15][16][17], the hoof wall consists of three layers: the stratum externum, stratum medium, and stratum internum. The stratum medium is the thickest of the three layers and is characterised by its tubular and intertubular horn structure.…”
Section: Introductionmentioning
confidence: 99%
“…Tissue homeostasis is possible due to the presence of ESCs, which have the capacity both for self‐renewal and generation of differentiated cells of the epidermal tissue (Blanpain and Fuchs 2009). In the case of the equine hoof, continuous growth is necessary to replace hoof lost at the ground surface (Daradka and Pollitt 2004). This growth is supported mainly by proliferation of epidermal cells (ECs) of proximal (coronary) regions of the hoof, with very low levels of proliferation in mid‐lamellar regions, as demonstrated in ponies using 5‐bromo‐2′‐deoxyuridine (BrdU) incorporation (Daradka and Pollitt 2004).…”
Section: Introductionmentioning
confidence: 99%
“…10,11 The PEL-types I and II could have been the predominant morphologic type of PEL within tissue sections because these types were detected grouped together, whereas PEL-type III was detected on its own. 10,11 The PEL-types I and II could have been the predominant morphologic type of PEL within tissue sections because these types were detected grouped together, whereas PEL-type III was detected on its own.…”
Section: Discussionmentioning
confidence: 99%